Microcontroller Based Obstacle Detection and Location Tracker Using Smart Stick System for Visual Impairment People - Mohd Shah, Muhammad Shakir Fahmi; Nik Ismail, Nik Mohd Asri (Evolution in Electrical and Electronic Engineering, 2023)
Visually impaired individuals face challenges in identifying obstacles while walking on the streets, making it a dangerous task. A proposed solution to this problem is a smart stick that can help them navigate their surroundings. In this paper, we suggest the use of a smart stick that is equipped with a pair of ultrasonic sensors. This project is designed to assist blind individuals in overcoming obstacles. This stick will have a sensor installed in it that will detect any item or person in front of it that have different positioning to detect obstacles at a different angle. The ultrasonic sensor 1 is programmed for a sensing distance of 80 cm and positioned at waist level while ultrasonic sensor 2 is programmed for a sensing distance of 50 cm positioned at ankle level for detecting the lower part of obstacles. When one of the ultrasonic sensors detects obstacles via transmitting sound waves, it will trigger the output component such as a buzzer and disc vibrating motor which alert the user to go on another route where there is no obstacle in front of them. The stick is also embedded with a navigation tracking system where the guardian can locate the real-time location of the stick user by using an application called Blynk with the help of a GPS module and WIFI. In conclusion, visually impaired individuals in becoming aware of obstacles or uneven surfaces that may cause harm in their surroundings. This can help to reduce the risk of injuries and enhance their ability to navigate their environment.